Zeghdοudi distribution in acceptance sampling plans based on truncated life tests with real data application - AlSultan, Rehab; Al-Omari, Amer (Decision Making: Applications in Management and Engineering, 2023)
The acceptance sampling plan (ASP) is one of the key statistics resources in the industrial sector. It entails the decision-making process for accepting or rejecting the products. The investigated quality parameter is the test unit’s mean lifespan. This study develops a new ASP for Zeghdοudi distribution (ZD) when the lifetime is shortened to a specific degree. The optimal plan parameters are accomplished by obtaining the minimum sample size mandatory to ensure the identified mean lifetime for fixing the consumer’s risk. Besides, the characteristic operating function (OCF) values for the ASP are displayed, and the producer’s risk is determined. Several helpful tables are developed for the suggested ASP based on the ZD for suitable employment. An actual data set is fitted to the Zeghdoudi model and other models to examine the applicability of the suggested ASP in the production sector.